'Can the subaltern speak?': COVID-19 and decolonial pedagogy in Palestinian universities. Issue 2 (3rd April 2021) - Hamamra, Bilal; Qabaha, Ahmad
ABSTRACT: The online mode of education has created a space for a decolonial pedagogy that allows student liberation from in-class education which perpetuates students' passivity. Drawing on Freire's concepts of banking education, dialogue and democracy, Said's various works and concepts, including 'margins' and 'centres', and students' testimonies concerning online and in-class modes of education, we contend that online education shatters the hegemony of instructors over the process of education. While students air their proclivity for emancipation from the hegemonic intricacy of the traditional classroom, instructors also highlight the importance of dialogue, research and enriching discussions that subvert the teacher-student hierarchy. While some instructors used to follow research and dialogue in class, they encountered challenges in introducing topics related to sexuality, politics and religion. However, these issues have shored up during online education as the emphasis on the part of instructors and students has been on constructing arguments rather than memorising materials. Thus, the online education we have been forced to adopt is a call for a paradigm shift in the sense that the traditional mode of education perpetuates students' passivity and suppression of their voices in ways that resonate with the suppression of Palestinian voices by the Israeli-settler colonialism.